A Proposed Method to Minimize the Flow Time Average and the Due Date Average in Sequence Problem - Ghazwan Mahmoud (Al-Rafidain Journal of Computer Sciences and Mathematics, 2010)
The problem tackled in this research is to propose a method to minimize the flow time average and the due date average to resolve the sequence problem. Assuming that we have a set of jobs, and every job has processing time and due date required to running by method that satisfy balance and minimize the flow time average and the due date average. The research presents the methods used to solve the former. The paper compares the new method with the Critical ratio (CR) method on a set of data generated by simulation by system (MATLAB). The results show a high efficiency and ease of use.